2018
DOI: 10.1002/ece3.3759
|View full text |Cite
|
Sign up to set email alerts
|

Which egg features predict egg rejection responses in American robins? Replicating Rothstein's (1982) study

Abstract: Rothstein (Behavioral Ecology and Sociobiology, 11, 1982, 229) was one of the first comprehensive studies to examine how different egg features influence egg rejection behaviors of avian brood parasite–hosts. The methods and conclusions of Rothstein (1982) laid the foundation for subsequent experimental brood parasitism studies over the past thirty years, but its results have never been evaluated with replication. Here, we partially replicated Rothstein's (1982) experiments using parallel artificial model egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 41 publications
(120 reference statements)
1
36
0
Order By: Relevance
“…This experiment was further replicated by Luro et al. (2018), which confirmed most of the original findings, but also showed that variation in egg size was less predictive than the other two features. Guigueno et al.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…This experiment was further replicated by Luro et al. (2018), which confirmed most of the original findings, but also showed that variation in egg size was less predictive than the other two features. Guigueno et al.…”
Section: Introductionsupporting
confidence: 72%
“…(2006) and Luro et al. (2018) that for an egg rejecter host, egg size has relatively less effect than other visual traits of the eggshell.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the individually repeatable eggshell coloration of female American Robins ( Turdus migratorius ), an occasional host of obligate brood‐parasitic Brown‐headed Cowbirds ( Molothrus ater ; Croston and Hauber 2015). American Robins have been the subject of many classic and recent parasitic egg‐rejection studies (e.g., Friedmann 1929, Rothstein 1982, Briskie et al 1992, Rasmussen et al 2009, Lang et al 2014, Abernathy and Peer 2015, Igic et al 2015, Carmody et al 2016, Luro and Hauber 2017, Luro et al 2018).…”
Section: Figmentioning
confidence: 99%
“…(1) egg spots do not contribute to egg recognition, and egg size is the main clue to identifying eggs (Mason and Rothstein 1986;Marchetti 2000;Langmore et al 2003); (2) spot patterns and egg colors are more important than egg size for egg recognition (Rothstein 1978;Lawes and Kirkman 1996;Igic et al 2015;Antonov et al 2006); (3) both egg colors and spot patterns affect egg rejection behavior by the host, but the egg colors are more important than the spot patterns (Lahti and Lahti 2002;Spottiswoode and Stevens 2010;Luro et al 2018); (4) egg spot patterns are more important than egg colors for egg recognition (Underwood and Sealy 2006;López-De-Hierro and Moreno-Rueda 2009;de la Colina et al 2012;Šulc et al 2016); and (5) spots on the blunt pole of the egg provide a cue for egg recognition (Lahti and Lahti 2002;Polačiková et al 2007Polačiková and Grim 2010). There were so many different signals influencing the host's response.…”
Section: Discussionmentioning
confidence: 99%